Sport-Related Concussion: Factors Associated With Prolonged Return to Play - Asplund, C. A.; McKeag, D. B.; Olsen, C. H. (Clinical Journal of Sport Medicine, 2004)
Objective: To assess predictive value of concussion signs and symptoms based on return-to-play timelines. Design: Physician practice study without diagnosis that includes presentation, initial and subsequent treatment, and management of concussion. Setting: National multisite primary care sports medicine provider locations. Participants: Twenty-two providers at 18 sites; 101 athletes (91 men, 10 women in the following sports: 73 football, 8 basketball, 8 soccer, 3 wrestling, 2 lacrosse, 2 skiing, 5 others; 51 college, 44 high school, 4 professional, and 2 recreational). Main Outcome Measurements: Duration of symptoms, presence of clinical signs, and time to return to play following concussion. Results: One hundred one concussions were analyzed. Pearson [chi]2 analysis of common early and late concussion symptoms revealed statistical significance (P < 0.05) of headache >3 hours, difficulty concentrating >3 hours, any retrograde amnesia or loss of consciousness, and return to play >7 days. There appeared to be a trend in patients with posttraumatic amnesia toward poor outcome, but this was not statistically significant. Conclusions: When evaluating concussion, symptoms of headache >3 hours, difficulty concentrating >3 hours, retrograde amnesia, or loss of consciousness may indicate a more severe injury or prolonged recovery; great caution should be exercised before returning these athletes to play.